Sudden infant death syndrome in Brazil: fact or fancy? - Woida, Francesca Maia; Saggioro, Fabiano Pinto; Ferro, Maria Alice Rossato; Peres, Luiz Cesar (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: The true incidence of sudden infant death syndrome (SIDS) in Brazil is unknown. The aim here was to identify SIDS cases in the city of Ribeirão Preto, State of São Paulo, between 2000 and 2005, in order to estimate its incidence. DESIGN AND SETTING: Retrospective analysis of data on live births and infant deaths in Ribeirão Preto and from autopsies of infants performed at the Death Verification Service of the Interior (SVOI) between 2000 and 2005. RESULTS: There were 47,356 live births and 537 deaths, with infant mortality rates ranging from 12.9‰ to 10.9‰ of live births. Among the 24 infants who died possibly due to SIDS and who were autopsied at the SVOI, six were from families living in the municipality (0.13‰ of live births): three (50%) were diagnosed as SIDS, and one each (16.66%) as indeterminate cause, bronchoaspiration and cerebral edema. Two deaths occurred in the first month of life (33.33%) and one each (16.66%) at two, four, six and eight months. Two deaths each (33.33%) occurred in the months of February and December, one each in August and October (16.66%). Four cases (66.7%) occurred in the summer and one each (16.66%) in winter and spring. There was 5:1 predominance of males over females. CONCLUSIONS: The frequency of SIDS was lower than what has been reported worldwide and in the Brazilian literature, thus suggesting underdiagnosis, indicating the lack of any specific postmortem protocol for SIDS identification and showing the need to implement this.